Prediction the longevity of worm gears with Archimedean and evolventary worm - Чернець, М.В.; Ярема, Р.Я. (Problems of Tribology, 2014)
In according to the developed method the calculation of longevity of both types of worm gears was conducted. It was found that it is lineary related to the wear of teeth of worm wheel and is practically identical for both types of gears. Also the regularities of change of maximal contact preasures in the chosen points on the height of coil of worm were researched.